Facile Strategy to Access the Indolo[2,3-a]quinolizidine Framework: Synthetic Study on Tangutorine - Reddy, Chada Raji; Warudikar, Kamalkishor; Latha, Bellamkonda (Synthesis, 2019)
An asymmetric synthetic approach to indolo[2,3-a]quinolizidine framework has been developed involving Horner–Wadsworth–Emmons olefination and reductive amination as the key steps. Further, the developed strategy was explored towards the synthesis of tangutorine using Evans aldol reaction for the preparation of desired aldehyde.
Keywords: indolo[2,3-a]quinolizidine; Horner–Wadsworth–Emmons reaction; piperidine; tangutorine